(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The skin, sometimes known as the integumentary System is, in fact, the largest organ of the body. It performs many functions that are important in maintaining homeostasis in the body. Probably the most important of these functions is the control of body temperature. The skin also protects the body from physical damage and bacterial invasion. The skin has an array of sense organs which sense the external environment and also cells which can make vitamin D in sunlight. A study was undertaken of the prevalence, diagnosis and treatment of dermatological disorders in hospitalized dogs at Madras Veterinary College (MVC), Chennai, India from 1st May to 30th May, 2017. Total 220 cases were observed and recorded that had a dermatological problem. Among the dog pruritus (86%), alopecia (63%), scaling (77%), maculo-papular-pustular lesion (91%) were the most common presenting sign. A diagnosis or recommendation for treatment was done on the basis of the presenting clinical signs, physical examination and various diagnostic tests. In this study most of the cases were diagnosed by multiple and deep skin scrapings (100 cases) and by dermato-histopathology (70 cases). The most frequently diagnosed cases were Malassezia dermatitis, Demodicosis, Scabies and Tick infestation. Tick infestation accounted for the majority of the diagnoses. Systemic antibiotics were prescribed in 9% cases, systemic antifungal drugs were prescribed in 7% cases, systemic glucocorticoids were prescribed in 10% cases, antihistaminic in 6% cases and treatment with an ectoparasiticide was prescribed in 73% cases. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (1), 1-6